A Review on Biohazards Removal in Ethiopia: Efficacy of Existing Treatment Systems and Challenges - Chalachew Yenew; Muluken Azage Yenesew; Argaw Ambelu; Gashaw Melkie Bayeh; Almaw Genet Yeshiwas (Environmental Health Insights)
Background: Wastewater treatment is crucial to protecting public health and the environment by removing Biohazards. In Ethiopia, however, significant research gaps limit progress, especially regarding the efficiency of Biohazard removal in existing treatment facilities. This review evaluates the effectiveness of current treatment methods for Biohazard removal, highlights key challenges, and offers recommendations. Methods: This scoping review followed PRISMA guidelines, systematically searching databases like NLM. Science Direct, HINARI and Scopus for Biohazard removal studies in Ethiopia, with independent reviewers screening and analyzing relevant data to identify key challenges. Results: Out of 1218 studies initially recorded by title and abstract, only 11 articles were selected for analysis. The Activated Sludge Process emerged as a highly effective system, achieving 85% to 95% removal of antimicrobial resistance (AMR) and total coliforms. Other methods, such as the Conventional Activated Sludge, and Anaerobic-Aerobic Reactors, demonstrated promising results but were found only in select locations. However, the widely adopted Oxidation Ponds, Ethiopia’s most common wastewater treatment system, showed the lowest AMR removal efficiency, at just 30% to 50%. Significant challenges, including inadequate infrastructure, high operational costs, and weak regulatory enforcement. Conclusions and recommendations: The review underscores the need for affordable wastewater treatment in Ethiopia, highlighting challenges such as inadequate infrastructure and high costs. To enhance effectiveness and reduce public health risks from Biohazards like AMR, recommendations include adopting cost-effective treatment technologies, strengthening regulatory frameworks, increasing public awareness, promoting corporate responsibility, and investing in infrastructure for sustainable wastewater management.